DFT Modelling of Tripeptides (Lysine-Tryptophan-Lysine) Interacting with Single Walled Carbon Nanotubes - Navaratnarajah Kuganathan (E-Journal of Chemistry)
Model calculations are performed to predict the nature of interaction between SWNT and a tripeptide (Lys-Trp-Lys) and to calculate the binding energies and charge transfer between these two species using density functional theory. DFT calculations indicate that the interaction is of a non covalent nature. Minimal charge transfer is observed between SWNT and Lys-Trp-Lys.